Magic Performances – When Explained in Psychic Terms by University Students - Lesaffre, Lise; Kuhn, Gustav; Abu-Akel, Ahmad; Rochat, Déborah; Mohr, Christine (Frontiers in Psychology, 2018)
Paranormal beliefs (PBs), such as the belief in the soul, or in extrasensory perception, are common in the general population. While there is information regarding what these beliefs correlate with (e.g., cognitive biases, personality styles), there is little information regarding the causal direction between these beliefs and their correlates. To investigate the formation of beliefs, we use an experimental design, in which PBs and belief-associated cognitive biases are assessed before and after a central event: a magic performance (see also Mohr et al., 2018). In the current paper, we report a series of studies investigating the “paranormal potential” of magic performances (Study 1, N = 49; Study 2, N = 89; Study 3, N = 123). We investigated (i) which magic performances resulted in paranormal explanations, and (ii) whether PBs and a belief-associated cognitive bias (i.e., repetition avoidance) became enhanced after the performance. Repetition avoidance was assessed using a random number generation task. After the performance, participants rated to what extent the magic performance could be explained in psychic (paranormal), conjuring, or religious terms. We found that conjuring explanations were negatively associated with religious and psychic explanations, whereas religious and psychic explanations were positively associated. Enhanced repetition avoidance correlated with higher PBs ahead of the performance. We also observed a significant increase in psychic explanations and a drop in conjuring explanations when performances involved powerful psychic routines (e.g., the performer contacted the dead). While the experimentally induced enhancement of psychic explanations is promising, future studies should account for potential variables that might explain absent framing and before–after effects (e.g., emotion, attention). Such effects are essential to understand the formation and manipulation of belief.